2020
DOI: 10.19128/turje.643785
|View full text |Cite
|
Sign up to set email alerts
|

Developing biomimicry STEM activity by querying the relationship between structure and function in organisms

Abstract: The theme that structure determines function is one of the most significant cornerstones in understanding natural sciences. On the other hand, recently revised science curriculum in Turkey has emphasized science and engineering practices to help students be able to converge science with the other disciplines by applying theory into practice and product; but there is not an emphasis on the repeating patterns and relationships between structure and function for natural and built systems at any grades. In order t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Additionally, it inspires students to find economical, efficient, and sustainable solutions for technical challenges from nature (Nagel et al, 2019). Besides being a powerful problem-solving approach, bio-inspired design is interdisciplinary (Snell-Rood and Smirnoff, 2023) and can be used to broaden participation and engagement from underrepresented groups, especially women, within engineering disciplines (Gencer et al, 2020).…”
Section: Bio-inspired Designmentioning
confidence: 99%
“…Additionally, it inspires students to find economical, efficient, and sustainable solutions for technical challenges from nature (Nagel et al, 2019). Besides being a powerful problem-solving approach, bio-inspired design is interdisciplinary (Snell-Rood and Smirnoff, 2023) and can be used to broaden participation and engagement from underrepresented groups, especially women, within engineering disciplines (Gencer et al, 2020).…”
Section: Bio-inspired Designmentioning
confidence: 99%
“…Researchers have revealed that the biomimicry approach can be used in STEM activities, can be effective in the design and analysis processes of interdisciplinary projects and will improve scientific research skills (Canbazoğlu-Bilici et al 2021). Similarly, Gencer et al (2020) pointed out that for biomimicry and STEM activities, students' examination of books, viewing documentaries, collecting data, interpreting, developing models, explaining scientific concepts, sharing their ideas, and enriching these ideas by discussing with their peers improve their scientific research skills and enable them to be part of the active learning process.…”
Section: Figure 4 Distribution Of Subdomains Associated With Learning...mentioning
confidence: 99%
“…The amalgamation of BID helps to break down traditional barriers between disciplines making engineering more accessible and appealing to all students, especially women [8]. Furthermore, BID activities compel students to examine nature deeply for novel, creative, and sustainable design solutions while heightening students' views about the natural world and supporting their understanding of the EDP [8], [10], [13], [14], [15].…”
Section: Biologically Inspired Design (Bid) In Pre-college Engineeringmentioning
confidence: 99%
“…In pre-college education, several studies have explored BID integration in the EDP across formal and informal settings [10], [11], [13], [14], [15]. Laut et al [13] explored middle school students' interest in STEM subjects, especially engineering-related concepts, after engaging in after-school activities.…”
Section: Biologically Inspired Design (Bid) In Pre-college Engineeringmentioning
confidence: 99%
See 1 more Smart Citation